Trafalgar Square, Barbados. W. I. - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
This picture shows a scene in Trafalgar Square, Bridgetown, St. Michael, Barbados. A busy wharf side scene where dozens of boats are docked, shows people going about their business. The "ECAF' building is prominent in the photo. A number of flags are raised around the docked boats. In the fore ground a bus and a red car are headed down the street. Info. At the back: CTD £12 64885-B Pub. By Picture-Point Publications, New York, N. Y. DEXTER PRESS, INC WEST. NYACK NEW YORK STAMP: 1 BARBADOS Post Office 4:00 PM, 21 JAN. 1963 STAMP: 12 Cents Barbados STAMP: AIR MAIL "Frank Stonaski. 2551 E. Madison Street, Phila. 34 ...... U. S. A. Lots to see- do & places to go all very interesting. Charles"
Landscape, colour, 4 x 6 in.
Keywords: Flags; Buildings; People; Vehicles; Cityscapes; Cities and towns; Piers and wharves; Trafalfar Square